Epidemiological trends of hand osteoarthritis from 1990 to 2019: Estimates from the 2019 Global Burden of Disease study - Wan, Junlai; Qian, Xiaoyuan; He, Zhiyi; Zhu, Ziqing; Cheng, Peng; Chen, Anmin (Frontiers in Medicine, 2022)
Background Hand osteoarthritis (OA) is a chronic progressive disease characterized by disabling pain in the hand, with a high clinical burden. This study is designed to assess the epidemiological patterns of hand OA from 1990 to 2019 and analyze its secular trends based on sex, age, and socio-demographic index (SDI) at global, regional, and national levels. Methods Data on the incidence and disability-adjusted life years (DALYs) of hand OA were extracted from the 2019 Global Burden of Disease (GBD), and their respective age-standardized rates (ASRs) were calculated. The estimated annual percentage changes (EAPCs) in ASR were calculated to assess the prevalent trends of the incidence and DALYs of hand OA over the recent three decades. The relationship between ASR and SDI was analyzed by Pearson's correlation analysis. Results The incidence of hand OA increased from 371.30 million in 1990 to 676.02 million in 2019, increasing by 82.07%, whereas its age-standardized incidence rate (ASIR) decreased, with a downward trend [EAPC = −0.34; 95% confidence interval: −0.39–−0.28]. With the changes in age, the incidence of hand OA exhibited a unimodal distribution before 70 years of age, peaking at 50–54 years, while its incidence had an upward trend in the >70 years age groups. Overall, hand OA-related DALYs increased in the recent 30 years. Meanwhile, its annual age-standardized DALY rate decreased, with EAPCs of −0.35 (95% CI, −0.38 –−0.32). The DALYs increased with age. In 2019, the ASIR and age-standardized DALY rate were positively associated with the SDI regions. The incidence and DALYs presented predominance in female patients. The burden of hand OA over the recent three decades displayed obvious geographical diversity. Conclusion The incident cases of hand OA increased globally from 1990 to 2019, while the ASIR and age-standardized DALY rate decreased. However, in many countries and regions, there was a rising trend of ASR related to incidence and DALYs. In addition, the prevalence revealed geographical, sex, and age diversity. Thus, governments and medical institutions should reallocate medical resources based on the epidemiological characteristics of hand OA.